2010
DOI: 10.5034/inquiryjrnl_47.01.81
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Ambulance Diversion on Heart Attack Deaths

Abstract: Hospital ambulance diversions are prevalent and increasing nationwide as emergency departments experience growing congestion. Using negative binomial regressions, this paper links the number of acute myocardial infarction (AMI) deaths to the level and extent of diversion in the five boroughs of New York City. The results indicate that both high levels of ambulance diversion and simultaneous diversion across hospitals are associated with increasing numbers of deaths from AMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…As we show at a granular level in this paper, this is not a tenable assumption. In addition, there have been various condition specific studies in the medical community demonstrating that delays can result in an increase in mortality (de Luca et al 2004, Chan et al 2008, Buist et al 2002, Yankovic et al 2010) and/or extend patient Length-of-stay (LOS) (Chalfin et al 2007, Renaud et al 2009, Rivers et al 2001). …”
Section: Standard Queueing Models Fall Shortmentioning
confidence: 99%
See 1 more Smart Citation
“…As we show at a granular level in this paper, this is not a tenable assumption. In addition, there have been various condition specific studies in the medical community demonstrating that delays can result in an increase in mortality (de Luca et al 2004, Chan et al 2008, Buist et al 2002, Yankovic et al 2010) and/or extend patient Length-of-stay (LOS) (Chalfin et al 2007, Renaud et al 2009, Rivers et al 2001). …”
Section: Standard Queueing Models Fall Shortmentioning
confidence: 99%
“…They find that the median hospital LOS and 28-day mortality rate is nearly twice as high for delayed patients. The order of magnitude for delay can be in minutes as in the case of cardiac patients (de Luca et al 2004, Buist et al 2002, Yankovic et al 2010, Chan et al 2008 or up to 5 days for burn-injured patients (Sheridan et al 1999). …”
Section: Related Literaturementioning
confidence: 99%
“…We identified a simulation study of a community hospital ED which found that the effect of diversion on waiting room times is quite small (2 minute reduction for every percentage point increase of time on diversion) 30. If this finding can be confirmed in other simulation and observational studies, it is unlikely that the small decrease in waiting room times from ambulance diversion could outweigh the unintended consequences of prolonged transport times and possibly worse outcomes of diverted patients 6,7,10…”
Section: Discussionmentioning
confidence: 99%
“…AD is known to reduce hospital revenues, increase patient transport times, and reduce ambulance availability (9)(10)(11)(12)(13)(14)(15). More recently, AD has been linked to increased mortality and a delay in the time to thrombolysis in patients with acute myocardial infarction (16,17). AD may have greater negative impact on vulnerable populations like the uninsured, those on public insurance, the elderly, and the critically ill, as these populations disproportionately use ambulance transport (18).…”
Section: Introductionmentioning
confidence: 98%